Malic Acid in Wine: Origin, Function and Metabolism during Vinification - Volschenk, H.; van Vuuren, H.J.J.; Viljoen-Bloom, M. (South African Journal of Enology and Viticulture, 2017)
The production of quality wines requires a judicious balance between the sugar, acid and flavour components of wine. L-Malic and tartaric acids are the most prominent organic acids in wine and play a crucial role in the winemaking process, including the organoleptic quality and the physical, biochemical and microbial stability of wine. Deacidification of grape must and wine is often required for the production of well-balanced wines. Malolactic fermentation induced by the addition of malolactic starter cultures, regarded as the preferred method for naturally reducing wine acidity, efficiently decreases the acidic taste of wine, improves the microbial stability and modifies to some extent the organoleptic character of wine. However, the recurrent phenomenon of delayed or sluggish malolactic fermentation often causes interruption of cellar operations, while the malolactic fermentation is not always compatible with certain styles of wine. Commercial wine yeast strains of Saccharomyces are generally unable to degrade L-malic acid effectively in grape must during alcoholic fermentation, with relatively minor modifications in total acidity during vinification. Functional expression of the malolactic pathway genes, i.e. the malate transporter (mae1) of Schizosaccharomyces pombe and the malolactic enzyme (mleA) from Oenococcus oeni in wine yeasts, has paved the way for the construction of malate-degrading strains of Saccharomyces for commercial winemaking.